Effective software testing a developer's guide - Aniche, Maurício (Manning Publications, 2022)
Written for the working developer, it offers state-of-the-art software testing techniques. Perfect for training the next generation of effective software testers. From the Foreword by Dr. Arie Van Deursen Go beyond basic testing! Great software testing makes the entire development process more efficient. This book reveals a systemic and effective approach that will help you customize your testing coverage and catch bugs in tricky corner cases. In Effective Software Testing you will learn how to: Engineer tests with a much higher chance of finding bugs Read code coverage metrics and use them to improve your test suite Understand when to use unit tests, integration tests, and system tests Use mocks and stubs to simplify your unit testing Think of pre-conditions, post-conditions, invariants, and contracts Implement property-based tests Utilize coding practices like dependency injection and hexagonal architecture that make your software easier to test Write good and maintainable test code Effective Software Testing teaches you a systematic approach to software testing that will ensure the quality of your code. It's full of techniques drawn from proven research in software engineering, and each chapter puts a new technique into practice. Follow the real-world use cases and detailed code samples, and you'll soon be engineering tests that find bugs in edge cases and parts of code you'd never think of testing! Along the way, you'll develop an intuition for testing that can save years of learning by trial and error. about the technology Effective testing ensures that you'll deliver quality software. For software engineers, testing is a key part of the development process. Mastering specification-based testing, boundary testing, structural testing, and other core strategies is essential to writing good tests and catching bugs before they hit production. about the book Effective Software Testing is a hands-on guide to creating bug-free software. Written for developers, it guides you through all the different types of testing, from single units up to entire components. You'll also learn how to engineer code that facilitates testing and how to write easy-to-maintain test code. Offering a thorough, systematic approach, this book includes annotated source code samples, realistic scenarios, and reasoned explanations. about the audience The Java-based examples illustrate concepts you can use for any object-oriented language. about the author Dr. Maur©Ưcio Aniche is the Tech Academy Lead at Adyen and an Assistant Professor in Software Engineering at the Delft University of Technology. The combination of theory and practice shows the depth of Mauricio's experience as an academic and as a working programmer! From the Foreword by Steve Freeman Whether you're a developer, tester, or student, you'll find this text an essential part of your work. James McKean Wood, Trimble PPM The first book I've read where I finally understood how to write a good unit test, and how to pair it with testable code.
Online resource; title from title details screen (O'Reilly, viewed August 23, 2022)
Keywords: Computer programs -- Testing; Logiciels; Essais; Computer programs; Testing; Instructional films; Internet videos; Nonfiction films; Films de formation; Films autres que de fiction; Vidéos sur Internet